Risk Based Technologies - Varde, Prabhakar V.; Prakash, Raghu V.; Joshi, Narendra S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents selected topics in implementing a risk-based approach for complex engineering systems in general, and nuclear plants in particular. It addresses gap areas in implementing the risk-based approach to design, operation and regulation, covering materials reliability, digital system reliability, software reliability, human factor considerations, condition monitoring and prognosis, structural aspects in risk-based design as well as the application aspects like asset management for first-of-their-kind projects, strategic management and other academic aspect. Chapters are authored by renowned experts who address some of the identified challenges in implementation of risk-based approach in a clear and cogent manner, using illustrations, tables and photographs for ease of communication. This book will prove useful to researchers, professionals, and students alike.
Chapter 1: Introduction -- Chapter 2: Materials Reliability -- Chapter 3: Structural Risk Assessment -- Chapter 4: Software risk and asset management -- Chapter 5: Human Factor Engineering for Complex Engineering Scenarios -- Chapter 6: Reliability and risk engineering - Academic aspects -- Chapter 7: Condition Monitoring and Prognosis - An asset Management Approach -- Chapter 8: Structural Reliability -- Chapter 9: Risk Management in First of its Kind Mega Project - A Case Study on Indian PFBR -- Chapter 10: Design for Reliability Approach to Electronics in Nuclear Plant Environment -- Chapter 11: Passive thermal hydraulic system reliability - AHWR Challange -- Chapter 12: Risk and Reliability Management Approach to Strategic System -- Chapter 13: Fatigue & Fracture Risk Assessment.
Keywords: Security systems; Nuclear engineering; Aerospace engineering; Astronautics; Dynamics; Nonlinear theories; Security Science and Technology; Nuclear Energy; Aerospace Technology and Astronautics; Applied Dynamical Systems